Differential effects on TDP-43, piezo-2, tight-junction proteins in various brain regions following repetitive low-intensity blast overpressure - Heyburn, Lanier; Dahal, Shataakshi; Abutarboush, Rania; Reed, Eileen; Urioste, Rodrigo; Batuure, Andrew; Wilder, Donna; Ahlers, Stephen T.; Long, Joseph B.; Sajja, Venkatasivasai Sujith (Frontiers in Neurology, 2023)
Mild traumatic brain injury (mTBI) caused by repetitive low-intensity blast overpressure (relBOP) in military personnel exposed to breaching and heavy weapons is often unrecognized and is understudied. Exposure to relBOP poses the risk of developing abnormal behavioral and psychological changes such as altered cognitive function, anxiety, and depression, all of which can severely compromise the quality of the life of the affected individual. Due to the structural and anatomical heterogeneity of the brain, understanding the potentially varied effects of relBOP in different regions of the brain could lend insights into the risks from exposures. In this study, using a rodent model of relBOP we showed the differential expression of various neuropathological proteins like TDP-43, tight junction proteins (claudin-5, occludin, and glial fibrillary acidic protein (GFAP)) and a mechanosensitive protein (piezo-2) in different regions of the brain at different intensities and frequency of blast. Our key results include i) significant increase in claudin-5 after 1x blast of 6.5 psi in all three regions and no definitive pattern with higher number of blasts, ii) significant increase in piezo-2 at 1x followed by significant decrease after multiple blasts in the cortex, iii) significant increase in piezo-2 with increasing number of blasts in frontal cortex and mixed pattern of expression in hippocampus and iv) mixed pattern of TDP-3 and GFAP expression